Reduced prefrontal-temporal cortical activation during verbal fluency task in obsessive-compulsive disorder: A multi-channel near-infrared spectroscopy study. (February 2019) - Liao, Jinmin; Li, Tian; Dong, Wentian; Wang, Jiuju; Tian, Ju; Liu, Jin; Quan, Wenxiang; Yan, Jun
Abstract: Functional neuroimaging studies by near-infrared spectroscopy (NIRS) have focused on the role of the prefrontal cortex (PFC) in the pathophysiology of obsessive-compulsive disorder (OCD). However, the reported areas in the PFC were inconsistent in OCD, and correlations between hemodynamic response and clinical symptoms have not been investigated. This study aimed to evaluate the hemodynamic response related to the verbal fluency task (VFT) and assess the relationship between activation and clinical status in OCD patients using a 52-channel NIRS with a wide coverage over the prefrontal and temporal cortices. Seventy patients with OCD and 70 age-, gender- and education level-matched healthy control subjects were examined by NIRS. The relative concentration changes of oxygenated hemoglobin ([oxy-Hb]) were measured. The Yale-Brown obsessive-compulsive scale (Y-BOCS) was used to evaluate the severity of OCD symptoms. Compared to healthy controls group, OCD patients showed smaller [oxy-Hb] changes in most areas of the prefrontal and temporal cortex, including the bilateral orbitofrontal cortex (OFC), right dorsolateral prefrontal cortex (DLPFC), bilateral inferior prefrontal cortex (IPFC), bilateral frontopolar cortex (FPC), left superior temporal gyrus (STG), and bilateral middle temporal gyrus (MTG). Furthermore, the [oxy-Hb] changes in the right FPC were negatively correlated with the Y-BOCS obsessions score and Y-BOCS total score, and the [oxy-Hb] changes in the left OFC were negatively correlated with the Y-BOCS compulsions score. These results suggest that patients with OCD have reduced prefrontal-temporal cortex hemodynamic responses, and that the abnormalities of brain activation were associated with the severity of OCD symptoms. Highlights: Activated areas in obsessive-compulsive disorder were smaller than healthy controls. Activated strengths were lower in most areas of the prefrontal and temporal cortex. Activation of right frontopolar cortex was negatively correlated with obsessions. Activation of left orbitofrontal cortex was negatively correlated compulsions.